2014
DOI: 10.5194/acp-14-8763-2014
|View full text |Cite
|
Sign up to set email alerts
|

On the submicron aerosol distributions and CCN number concentrations in and around the Korean Peninsula

Abstract: Abstract. Total number concentrations of particles having a diameter larger than 10 nm (N CN ), cloud condensation nuclei at several supersaturation (S) values (N CCN ) and number size distributions of particles with 10-414 nm diameter were measured in Seoul between 2004 and 2010. Overall average values of N CN and geometric mean diameter were 17 811 ± 5581 cm −3 and 48 ± 6 nm. Average N CCN at 0.4, 0.6 and 0.8 % S were 4145 ± 2016, 5323 ± 2453 and 6067 ± 2780 cm −3 and corresponding N CCN / N CN were 0.26 ± 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 42 publications
3
36
1
Order By: Relevance
“…H . Kim et al . [2014] found that aerosol hygroscopicity varied to a large extent along the western coast of Korea, depending on whether air masses come from China (higher hygroscopicity) or Korea/Japan (lower hygroscopicity).…”
Section: Aerosols and Climate Change In Asia: An Observational Perspementioning
confidence: 99%
“…H . Kim et al . [2014] found that aerosol hygroscopicity varied to a large extent along the western coast of Korea, depending on whether air masses come from China (higher hygroscopicity) or Korea/Japan (lower hygroscopicity).…”
Section: Aerosols and Climate Change In Asia: An Observational Perspementioning
confidence: 99%
“…This factor is based on observations showing that reduction in aerosol loading between polluted days and clean days is generally tenfold over Seoul and Houston (Lance et al, 2009;Kim et al, 2014). This simulation is referred to as the low-aerosol-Seoul run for the Seoul case and the low-aerosol-Houston run for the Houston case.…”
Section: The Csrm Simulationsmentioning
confidence: 99%
“…For that reason, emphasis was given to the quality check of the CCN number 20 concentrations that had not previously been published in most cases. Exceptions are the data from Seoul (Kim et al, 2014) and ATTO , whereby the latter station is not included in Schmale et at. (2017).…”
Section: Data Treatment and Quality Assurancementioning
confidence: 99%